RANCANG BANGUN SISTEM KONTROL OTOMATIS SENSOR KELEMBABAN TANAH PADA MEDIA TANAM POLYBAG - Deivana Kamagi; David P. Rumambi; Leo H. Kalesaran (COCOS, 2023)
AbstactSoil Moisture is the amount of water stored between the pores of the soil. Soilmoisture conditions are very dynamic, this is caused by absorption through the soilsurface of transpiration and percolation. Knowing the differences in surface soilmoisture can help optimize soil management in a field, so that productivity can bemaintained. Water obtained by the soil consists of two ways, namely naturally fromrainwater and artificial processes such as irrigation. One of the factors that affectsoil moisture is watering. Watering is something that cannot be released inmaintaining soil moisture. One effort that can be done is to provide irrigation water,namely by using an automatic system based on a microcontroller using sensors to dowatering according to water needs without having to use human power/operators.This research was conducted at the Greenhouse of the Faculty of Agriculture,University of Sam Ratulangi for one day. Data collection was carried out at intervalsof two hours with three treatments namely A 70% humidity standard, B 80% humiditystandard, C 90% humidity standard indicating that the irrigation system using theArduino Uno microcontroller can detect changes/decreases in soil moisture in theexperimental polybags, and can respond and command watering activities to restorerelative humidity conditions.Keyword : soil moisture, humidity, automatic control